Lethal pulmonary hemorrhage syndrome due to Leptospira infection transmitted by pet rat - Ludwig, Bernd (IDCases, 2017)
Human infection with Leptospira interrogans can be life-threatening. Multiple organ involvement frequently presents with liver and kidney failure, less commonly including severe hemolysis and pulmonary hemorrhage syndrome. Here, we present a fulminant case of leptospirosis presenting with hemolysis and pulmonary hemorrhage. A formerly healthy 34 year old patient presented to a rural hospital with dyspnea and hemoptysis after a week of influenza-like symptoms. Initial assessment revealed severe sepsis, acute kidney failure and severe hemolysis. Within the next 29 h, a multi-organ failure developed, which could eventually not be reversed despite mechanical ventilation, venovenous extracorporeal membrane oxygenation, continuous renal replacement therapy, plasmapheresis and extracorporeal cytokine absorbent therapy. The diagnosis of leptospirosis was made after the patient died. The transmitting animal was a pet rat. Leptospirosis has to be considered in case of rapid multi-organ failure presenting with pulmonary hemorrhage.